Multimedia Berbasis Video Tutorial Pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) Kelas X - Srinarti Srinarti; Joko Kuswanto (Komputer dan Pembelajaran, 2023)
This research aims to produce multimedia based on video tutorials on the subject of physical education, sports and health (PJOK) class X. Data collection techniques use expert validation sheets and field trials, in the form of questionnaires and documentation. Based on the results of the validation, the three experts obtained the "Good" eligibility criteria with an average score of 86.29%, and the large-scale field trial obtained the "Very Good" eligibility criteria with an average of 86.01%. The results of this data show that the products developed are valid and practical. This multimedia development research based on video tutorials is expected to be a learning medium for physical education and sports subjects and can be useful for teachers and students